Sosialisasi Pembuatan Dan Manfaat Hand Sanitizer Daun Sirih Untuk Aplikasi Pencegahan Penularan Covid-19: Socialization of Making and Benefits of Betel Leaf Hand Sanitizer For Transmission Prevention Applications of Covid-19 - Hasrin Lamote; Zul Arham; Ismaun Ismaun (Jurnal Mandala Pengabdian Masyarakat, 2020)
This activity was carried out to provide guidance and knowledge to students and teachers of Madrasah Aliyah (MA) DDI Al-Ihsan Kendari about the making process and benefits of the Betel Leaf Hand Sanitizer for the application of preventing the transmission of Coronavirus Disease 19 (Covid-19). The method of implementing the activity consisted of a Focus Group Discussion (FGD) and the practice of making hand sanitizer fluids. The output of the activity is that students and teachers get knowledge based on the latest research data on the potential of the betel plant as an antimicroorganism such as bacteria and viruses. In addition, students can independently make hand sanitizers at home or at school. During the activity, students and teachers gave many positive responses through question and answer both in FGD activities and practical activities.